PATHOGENESIS, DIAGNOSTIC AND MANAGEMENT OF TOXOPLASMOSIS - Yuliawati, Irma; Nasronudin, Nasronudin (Indonesian Journal of Tropical and Infectious Disease, 2015)
Toxoplasma gondii is an obligate intracellular parasite of protozoa groups, can infect humans and all warm-blooded animals, are  found in almost all locations around the world. Infection generally occurs orally through the consumption of animal products that are not perfectly cooked infected oocyst, parasite containing foods in the form of bradyzoite, contact with cat's feces containing oocysts or vertical transmission occurring through hematogenous placenta. Toxoplamosis can occur in acute or chronic. It divided into five categories, namely, toxoplasmosis in patients immunocompetent, toxoplasmosis in pregnancy, congenital toxoplasmosis, toxoplasmosis in immunocompromised patients and ocular toxoplasmosis. In each category of clinical manifestations of toxoplasmosis are often non-specific. Methods of diagnosis and interpretation are often different for each category. Toxoplasmosis can be diagnosed through a series of tests such as serology, PCR, histology parasites and parasite isolation. Treatment management of this disease requires a long time. Therapy depends on the category of infections as well as individual therapeutic response. The combination of pyrimethamine with sulfadiazine is the drug choice for toxoplasmosis.